2021
DOI: 10.1021/acsomega.1c04069
|View full text |Cite
|
Sign up to set email alerts
|

Direct Synthesis of Diamides from Dicarboxylic Acids with Amines Using Nb2O5 as a Lewis Acid Catalyst and Molecular Docking Studies as Anticancer Agents

Abstract: Several Lewis and Bronsted acid catalysts were tested for the synthesis of some targeted diamides with anticancer activity from dicarboxylic acids and amines under the same reaction condition. Among those catalysts, Nb2O5 showed the highest catalytic activity to the corresponding diamides. Nb2O5 shows water- and base-tolerant properties for which it gives the highest yield of the synthesized products. Here, we present a novel and sustainable method for the direct synthesis of diamides with anticancer activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The term pharmacological activity 42 refers to the bene cial effects of drugs on living organisms. The drug is meant to bind to a biological target.…”
Section: Bioactivity Score Of the Ligandmentioning
confidence: 99%
“…The term pharmacological activity 42 refers to the bene cial effects of drugs on living organisms. The drug is meant to bind to a biological target.…”
Section: Bioactivity Score Of the Ligandmentioning
confidence: 99%
“…It was reported that diamide, imidazole, and 1,2,4-triazinone derivatives as a template for antiproliferative agents have cytotoxic activities over several cancer cell lines [ 19 , 20 , 21 ]. The average IC 50 of imidazole RABI-112 IV over eight cancer cell lines was 14 nM, and it caused cells’ arrest at the G2/M phase of the cell cycle besides its detrimental effect on microtubule networks [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Amidation reactions are the most accomplished chemical processes in the pharmaceutical industry and drug discovery activities. [3][4][5][6] The world's leading pharmaceutical companies GSK, AstraZeneca and Pzer conducted a small survey of 128 drug candidate molecules, and from which, they found that around 10% of the reactions used in their synthesis involved an amide bond formation reaction. [7][8][9] A consecutive scheme for the synthesis of amides has emerged on amides and the coupling of activated carboxylic acid derivatives.…”
Section: Introductionmentioning
confidence: 99%